New feather mites of the subfamily Pterodectinae (Acari: Proctophyllodidae) from passerines and woodpeckers (Aves: Passeriformes and Piciformes) in Vietnam - Mironov, Sergey; Literak, Ivan; Hung, Nguyen Manh; Capek, Miroslav (Zootaxa, 2012)
Two new genera and nine new species of the feather mite subamily Pterodectinae (Proctophyllodidae) are described from passerines and woodpeckers in Vietnam: Dolichodectes furcilobus sp. n. from Copsychus malabaricus (Scopoli) (Muscicapidae), Montesauria abroscopi sp. n. from Abroscopus superciliaris (Blyth) (Cettiidae), M. macronoi sp. n. from Macronous gularis (Horsfield) (Timaliidae), M. pellornei sp. n. from Pellorneum ruficeps Swainson (Pellorneidae), M. phylloscopi sp. n. from Phylloscopus ricketti (Slater) (Phylloscopidae), M. seicerci sp. n. from Seicercus valentini (Hartert) (Phylloscopidae), Picipterodectes sasiae gen. n., sp. n. from Sasia ochracea Hodgson (Picidae), Proterothrix alcippeae sp. n. from Alcippe rufogularis (Mandelli) (Pellorneidae), and Vireodectes erporni gen. n., sp. n. from Erpornis zantholeuca (Blyth) (Vireonidae). The new genera Picipterodectes gen. n. and Vireodectes gen. n. belong to the Proterothrix generic group uniting archaic genera in the tribe Pterodectini. Brief comments on the current state of systematics of the genera Dolichodectes Park and Atyeo, 1971, Montesauria Oudemans, 1905 and Proterothrix Gaud, 1968 are provided. A new species group macronoi is established in the genus Montesauria.